Adaptation I-Adapt Measurement in The Context of Guidance and Counseling Teachers - Yuliati Hotifah; Nur Ainy Fardana Nawangsari; Nono Hery Yoenanto (Universitas Ahmad Dahlan, 2022)
This study aimed to obtain a standardized Indonesian version of the adaptability scale of guidance and counseling teachers. Adaptability consists of 8 dimensions: crisis, culture, work stress, interpersonal, physical, creative, learning, and uncertainty. The adaptation process is carried out using the International Test Commission (2016) reference. This adaptation involves 276 BK teachers. The research instrument is a statement item consisting of 55 items. The data analysis technique uses content analysis and constructs analysis. The content analysis used the CVI, while the construct analysis used CFA with the AMOS 21 program. The reliability test was based on internal consistency through the Cronbach Alpha coefficient. The results of the data analysis show that the CVR value meets the minimum parameters. There are 30 items that are proven to have a good fit model. The reliability coefficient of Cronbach's alpha individual variable adaptability measurement is .929.